Study on the Belt Mechanics Property of Belt Drive System During Critical Slip State - Liu Ying (Jixie chuandong)
In order to solve the problem of belt drive system energy loss during belt critical gross slip state,the V belt system is regarded as research subjects,the calculation formula of mechanical property in pulley wrap angle region is deduced,when critical gross slip state,combined with the V belts basis of structural parameters,finally,the belt total pressure and total friction formulas during the critical gross slip state are got by theoretical value derivation. The results show that with the ratio of slip occurs state angle / wrap angle increases,the total pressure between the belt and pulley show a trend of first increase then decrease; when the friction coefficient is small,with the ratio of slip occurs state angle / wrap angle increases,the total friction of the belt as a whole show a downward trend,when the friction coefficient is large,the total friction belts in the overall show a trend of first increase then decrease; through the study of the mechanical property of belt drive system during critical gross slip state,which can provide important significance for the subsequent control of the belt drive slippage and improve transmission efficiency.